68 Tentoonstellinge 69 : Kunstgalerij Imago Tielt. - Kunstgalerij Imago, Tielt (Tielt : Kunstgalerij Imago, 1969)
Verdegem, Jos ; De Pelsmaeker, Lieve ; Mendelson, Marc ; De Beul, Leo ; Halsberghe, Nicole ; Canestraro, Livia ; Depuydt, Stefaan ; Van de Velde, Berten ; Somville, Roger ; Driesschaert, Herwig ; Pauwels, Achiel ; etc.
Nederlands
boek